A novel H-bonding self-assembly heteromeric molecular duplex bearing host and guest energy transfer units as high-performance electroluminescent material. (February 2018) - Zhang, Cheng; Wang, Yi; Huang, Qingyu; Zhou, Jie; Huang, Yan; Zhao, Suling; Lu, Zhiyun
Abstract: Two oligoamide strands with complementary H-bonding sequences bearing4HB-NIM and4HB-CzNI were synthesized.4HB-NIM and4HB-CzNI could be self-assembled into a heterodimeric dyad (namely4HB-NIM-CzNI) via quadruple H-bond interactions. Photoluminescence measurements revealed that in both dilute solution and doped film states, more efficient host-guest energy transfer processes could be observed in the duplex4HB-NIM-CzNI than the physical blends of the small molecular guest reference compoundNIM and the host single strand4HB-CzNI, which should be attributed to the shortened spatial distances in4HB-NIM-CzNI . In addition, in comparison withNIM and the guest single strand4HB-NIM, 4HB-NIM-CzNI shows much higher photoluminescence quantum yield [0.53 vs 0.04 (NIM ) or 0.35 (4HB-NIM )] in neat-film state, indicative of the more alleviated concentration quenching of the guest fluorophore in4HB-NIM-CzNI than4HB-NIM andNIM . As a consequence, an organic light-emitting diode (OLED) with4HB-NIM-CzNI as the light-emitting dopant shows much more improved electroluminescent performance than its4HB-NIM -based reference OLED: with lower turn-on voltage (5.0 vs 5.9 V), higher maximum luminance (5260 vs 2980 cd m −2 ) and current efficiency (3.5 vs 3.0 cd A −1 ) as well as lower efficiency roll-off. All these results indicated that the integration of both host and guest fluorophores into H-bonding self-assembled material should be an effective strategy to construct high performance supramolecular electroluminescent materials. Highlights: H-bonding self-assembled supramolecular material was synthesized. Integrated both host and guest fluorophores into H-bonding self-assembled material. Investigated the energy transfer process in supramolecular material. Achieved relatively higher performance compare with counterpart molecula.